The BeHealthyR Study: a randomized trial of a multicomponent intervention to reduce stress, smoking and improve financial health of low-income residents in Rotterdam - Sara S. Shagiwal; Astrid Schop-Etman; Iris Bergwerff; Wil Vrencken; Semiha Denktaş (BMC, 2018)
Abstract Background Compared to higher socioeconomic status (SES) groups, those in lower SES groups are financially strained, experience higher rates of smoking-related morbidity, are in poorer health and have reduced life expectancy. This is especially true for the city of Rotterdam, where a large inequality in health is observed between low and high SES groups. The BeHealthyR study (Dutch: Grip en Gezondheid) is a randomized controlled trial (RCT) which will evaluate the impact of a theory-based multicomponent behavior intervention aiming to reduce stress, smoking, and improve financial health by means of a group-based stress management program combining cognitive and behavioral techniques, and nudges in low-SES residents living in Rotterdam. Methods The BeHealthyR study is a three-arm RCT. Between February 2018 and July 2019, low-SES participants who perceive stress, smoke, are financially strained and reside in Rotterdam (one of the four largest cities in The Netherlands) are recruited. Subsequently, participants are randomly assigned to either a stress management condition (SM), stress management with a buddy condition (SM-B) or a control condition (CC). Participants in the SM and SM-B conditions will attend four weekly group sessions (1.5 h/session) and a follow-up session eight weeks later. The SM condition includes psychoeducation and exercises, and cognitive and behavioral intervention techniques. Demographic data and objective measures will be collected at baseline (T0), four weeks post-baseline (T1), and twelve weeks post-baseline (T2). Primary outcome measures are to reduce stress, smoking and improve financial health. We hypothesize that low-SES participants in the intervention conditions, compared with those in the control condition, will experience less stress, smoke less and have improved financial health. Discussion This study is a group-based intervention which aims to investigate the effects of a theory-based behavioral change intervention employing several components on reducing stress, smoking, and improving financial health in low-SES residents living in Rotterdam. If effective, the findings from the present study will serve to inform future directions of research and clinical practice with regard to behavioral change interventions for low-SES groups. Trial registration ClinicalTrials.gov (ID: NCT03553979). Registered on January 1 2018.